Requests for internal review and the revised Aarhus Regulation - Pánovics, Attila (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2023)
This article examines the development of EU law in the context of access to justice guaranteed under the Aarhus Convention. It considers how the Court of Justice of the European Union and the Compliance Committee of the Convention (ACCC) interpret obligations arising under Article 9(3) of the Convention. When the EU ratified the Convention in 2005 it committed to guaranteeing broad access to justice in environmental matters at both national and Union levels. Until now, the 2006 Aarhus Regulation is the sole piece of EU legislation outside the provisions of the Treaties that was adopted for the purpose of providing the basis for access to justice in environmental matters at Union level. Unfortunately, the internal review procedure set out by the 2006 Aarhus Regulation has been interpreted so restrictively by the Court of Justice of the EU that its added value in striving for better access to courts remained ephemeral. The article discusses the findings of the ACCC on the EU’s non-compliance with Article 9(3) of the Convention, and highlights the recent legislative activities at EU level relating to access to justice in environmental matters. The application of the revised Aarhus Regulation will demonstrate whether the European Union has duly implemented its international obligations regarding access to justice in environmental matters.